Desinformación: aproximación conceptual, riesgos y remedios - Astudillo Muñoz, Jorge (Pontificia Universidad Católica del Perú, 2024)
The current work seeks to offer a general reflection on the phenomenon of misinformation in the digital age in order to raise awarenessabout the risks it poses to the normal development of democratic processes. Furthermore, it aims to emphasize the need to approach misinformation from various perspectives, in harmony with full respect for freedom of expression. The study intends to provide tools that allow the clear identification of misinformation, to point out some thoughts regarding the purposes that underlie the act of misinforming and to review the main stages of the misinformation process. It also strives to offer a more comprehensive understanding of the concept of misinformation, by proposing a distinction and identifying the connections between this activity and the communicative phenomenon of fake news. Later on, the analysis concentrates on the effects that misinformation has on democracy and the respect for human rights, particularly within the context of modern societies characterized by the use of ICTs. Lastly, a brief overview is presented of some of the tools that could be considered to confront misinformation, although the study will not delve into each of these remedies due to its length constraints.

El presente trabajo busca ofrecer una reflexión general sobre el fenómeno de la desinformación en la era digital con el fin de crear conciencia sobre los riesgos que representa para el normal desarrollo de los procesos democráticos. Además, busca destacar la necesidad de abordar la desinformación desde diversos ámbitos, en armonía con el pleno respeto de la libertad de expresión. El estudio pretende proporcionar herramientas quepermitan identificar claramente la desinformación, señalar algunas ideas respecto de las finalidades que subyacen a la actividad de desinformar y revisar las principales etapas del proceso de desinformación. También busca ofrecer una visión más acabada del concepto de desinformación, planteando una distinción e identificando las conexiones entre esta actividad y el fenómeno comunicativo de las fake news. Posteriormente, el análisis se centra en los efectos que la desinformación produce para la democracia y el respeto a los derechos humanos, especialmente en el marco de las sociedades modernas marcadas por el uso de las TIC. Por último, se ofrece un breve panorama sobre algunas de las herramientas que pueden ser consideradas para hacer frente a la desinformación, aunque no se profundizará en cadauno de estos remedios debido a los límites de extensión del estudio.
Disinformation: Conceptual Approach, Risks and Remedies
Keywords: Disinformation; Fake news; Internet; Social media; Democracy; Human rights; Desinformación; Noticias falsas; Internet; Redes sociales; Derechos humanos; https://purl.org/pe-repo/ocde/ford#5.05.01